2020
DOI: 10.1186/s12871-020-01058-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of caudal ketamine on minimum local anesthetic concentration of ropivacaine in children: a prospective randomized trial

Abstract: Background: Caudal ketamine has been shown to provide an effective and prolonged post-operative analgesia with few adverse effects. However, the effect of caudal ketamine on the minimum local anesthetic concentration (MLAC) of ropivacaine for intra-operative analgesia is unclear. Methods: One hundred and sixty-nine children were randomized to five groups: Group C (caudal ropivacaine only), Group K 0.25 (caudal ropivacaine plus 0.25 mg/kg ketamine), Group K 0.5 (caudal ropivacaine plus 0.5 mg/kg ketamine), Grou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…However, its effect on the quality of block is conflicting, ranging from incomplete motor block [66] to enhanced segmental spread [67]. The addition of ketamine to paediatric caudal epidurals prolongs postoperative analgesia with lidocaine [68], bupivacaine [69] and ropivacaine [70,71]. Ketamine facilitates intrathecal local anaesthetic sparing but its application may be limited by adverse central effects such as sedation, dizziness, nystagmus, dysphoria and nausea [72].…”
Section: Anaesthetic Adjunctsmentioning
confidence: 99%
“…However, its effect on the quality of block is conflicting, ranging from incomplete motor block [66] to enhanced segmental spread [67]. The addition of ketamine to paediatric caudal epidurals prolongs postoperative analgesia with lidocaine [68], bupivacaine [69] and ropivacaine [70,71]. Ketamine facilitates intrathecal local anaesthetic sparing but its application may be limited by adverse central effects such as sedation, dizziness, nystagmus, dysphoria and nausea [72].…”
Section: Anaesthetic Adjunctsmentioning
confidence: 99%
“…It has been shown that the use of ketamine in the caudal block resulted in prolonged analgesia and reduced postoperative analgesic demand, but that the minimum local anesthetic concentration (MLAC) of ropivacaine is necessary for intraoperative pain control does not change [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Later, the direct action of ketamine on sodium channels at peripheral nerve terminals was theorised [248]. Although ketamine does not play a significant role in pain management, the idea of using ketamine to induce local anaesthesia is intriguing and deserves further investigation [249][250][251][252].…”
Section: − Ketamine As a Local Anaestheticmentioning
confidence: 99%